A simple, high-resolution, non-destructive method for determining the spatial gradient of the elastic modulus of insect cuticle. Issue 145 (29th August 2018) - Eshghi, S h.; Jafarpour, M.; Darvizeh, A.; Gorb, S. N.; Rajabi, H.
Abstract : Nature has evolved structures with high load-carrying capacity and long-term durability. The principles underlying the functionality of such structures, if studied systematically, can inspire the design of more efficient engineering systems. An important step in this process is to characterize the material properties of the structure under investigation. However, direct mechanical measurements on small complex-shaped biological samples involve numerous technical challenges. To overcome these challenges, we developed a method for estimation of the elastic modulus of insect cuticle, the second most abundant biological composite in nature, through simple light microscopy. In brief, we established a quantitative link between the autofluorescence of different constituent materials of insect cuticle, and the resulting mechanical properties. This approach was verified using data on cuticular structures of three different insect species. The method presented in this study allows three-dimensional visualisation of the elastic modulus, which is impossible with any other available technique. This is especially important for precise finite-element modelling of cuticle, which is known to have spatially graded properties. Considering the simplicity, ease of implementation and high-resolution of the results, our method is a crucial step towards a better understanding of material–function relationships in insect cuticle, and can potentially be adapted for other graded biological materials.